Floating solar stills and floating solar-driven membranes: Recent advances and overview of designs, performance and modern combinations. (15th November 2022) - Rashid, Farhan Lafta; Al-Obaidi, Mudhar A.; Hussein, Ahmed Kadhim; Akkurt, Nevzat; Ali, Bagh; Younis, Obai
Highlights: This review is directed to evaluate the scope and limitations of floating solar stills and floating solar-driven membranes. Over 35 papers were reviewed to explain the concept of floating solar stills, solar-driven membranes, and related concepts. Floating solar stills and solar-driven membranes are effective in remote or rural coastal areas. Floating solar stills and floating solar-driven membranes have a future potential as small-scale desalination technology. Floating solar stills and solar-driven membranes can convert 90% of solar into vapor using an interfacial heating evaporator. Abstract: For life to exist on earth, there must be water. Freshwater resources are in short supply due to industrialization and the world's rapid population expansion. Growing water shortage argues that using passive solar stills is the best and most practical solution in the world's arid and semi-arid regions. For applications in distant or rural coastal areas, floating solar stills are an appropriate technique. To provide accessibility to a wider population, the gadget should be constructed using inexpensive materials that are easily accessible nearby. However, the low-cost materials typically do not have the optimum physical characteristics, which reduces the overall performance of solar stills. This study intends to deliver a comprehensive review that summarizes recent research developments and gives a rundown of experimental, numerical, and experimental and numerical studies on floating solar stills and floating solar-driven membranes. This article also looks at a few more setups, researched parameters, and result-finding issues. Research on floating solar is currently ongoing, and recommendations for further research projects have been made in light of the study's findings.